2020
DOI: 10.3389/fpsyg.2020.580620
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing Social Identity Theory in Corporate Social Responsibility: An Experimental Investigation

Abstract: Corporate social responsibility (CSR) is widely established by companies that aim to contribute to society and minimize their negative impact on the environment. In CSR research, employees’ reactions to CSR have extensively been researched. Social identity theory is often used as a theoretical background to explain the relationship between CSR and employee-related outcomes, but until now, a sound empirical examination is lacking, and causality remains unclear. CSR can unfold its effect mainly because of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…A closer examination of the (quasi-) experimental studies ( k = 14) revealed that most studies (71%) investigated the effect of CSR on attractiveness or turnover intentions (e.g., Zhang and Gowan, 2012 ; Bode et al, 2015 ; Joo et al, 2016 ). The results of three other experimental studies indicate that the effects of CSR on identification, engagement, commitment, job satisfaction, and OCB are causal (Ferreira and Real de Oliveira, 2014 ; Raub, 2017 ; Paruzel et al, 2020 ). In summary, for each outcome at least one study supports the notion of causal effects of CSR.…”
Section: Discussionmentioning
confidence: 95%
“…A closer examination of the (quasi-) experimental studies ( k = 14) revealed that most studies (71%) investigated the effect of CSR on attractiveness or turnover intentions (e.g., Zhang and Gowan, 2012 ; Bode et al, 2015 ; Joo et al, 2016 ). The results of three other experimental studies indicate that the effects of CSR on identification, engagement, commitment, job satisfaction, and OCB are causal (Ferreira and Real de Oliveira, 2014 ; Raub, 2017 ; Paruzel et al, 2020 ). In summary, for each outcome at least one study supports the notion of causal effects of CSR.…”
Section: Discussionmentioning
confidence: 95%
“…Also, organizational commitment is a strong antecedent of OCB (Bravo et al, 2017;Castro-González, Bande, & Kimura, 2019;Fu, Ye, & Law, 2014). Based on the given background and prior literature, CSR is projected to have relatively weaker relationships with employee behaviors like OCB De Roeck et al, 2016;Edwards & Kudret, 2017;Evans et al, 2011;Ng et al, 2019;Paruzel et al, 2020;Paruzel et al, 2021;Pivato et al, 2008;Zhang et al, 2014).…”
Section: Perceived Csr and Work Behavior 'Organizational Citizenship ...mentioning
confidence: 99%
“…Also, organizational commitment is a strong antecedent of OCB (Bravo et al, 2017; Castro‐González, Bande, & Kimura, 2019; Fu, Ye, & Law, 2014). Based on the given background and prior literature, CSR is projected to have relatively weaker relationships with employee behaviors like OCB (Choi & Yu, 2014; De Roeck et al, 2016; Edwards & Kudret, 2017; Evans et al, 2011; Ng et al, 2019; Paruzel et al, 2020; Paruzel et al, 2021; Pivato et al, 2008; Zhang et al, 2014). Hypothesis There is a positive association between employees' perceived CSR and OCB.Hypothesis The relationship between perceived CSR and behavioral outcome (OCB) is weaker than perceived CSR with emotional and attitudinal outcomes (organizational trust, pride, and commitment).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, individuals who value a company's CSR activities have positive feelings toward the corporate brand . Thus, customers are likely to maintain a positive personal identity by having a relationship with a corporate brand with a positive CSR perception (Paruzel et al, 2020). However, several previous studies have revealed CSR effects on customer citizenship behavior using social exchange theory, which emphasizes reciprocal relationships (Aljarah, 2020).…”
Section: Customers' Perceptions Of Csr and Customer Citizenship Behav...mentioning
confidence: 99%